2018
DOI: 10.1590/1414-431x20187065
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α inhibits SCF, ghrelin, and substance P expressions through the NF-κB pathway activation in interstitial cells of Cajal

Abstract: Ulcerative colitis is a chronic inflammatory disease of the colon where intestinal motility is disturbed. Interstitial cells of Cajal (ICC) are required to maintain normal intestinal motility. In the present study, we assessed the effect of tumor necrosis factor-alpha (TNF-α) on viability and apoptosis of ICC, as well as on the expression of stem cell factor (SCF), ghrelin, and substance P. ICC were derived from the small intestines of Swiss albino mice. Cell viability and apoptosis were measured using CCK-8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Moreover, YIL-781 attenuates prostate enlargement in HFP and TP BPH mice, WP1066 blocks ghrelin-induced cell proliferation and apoptosis inhibition, increased Bcl2 and decreased BAX expression also strengthens the evidence that Ghrelin promotes cell proliferations while inhibits apoptosis in the prostate gland through Jak2/STAT3 pathway. Effect of Ghrelin on apoptosis in prostate cells may be consistent with results in previous study that Ghrelin attenuated apoptosis of human micro vascular endothelial cells induced by high glucose/high lipid ( Liao et al, 2017 ),endothelial and vascular of cardiovascular system ( Lilleness and Frishman, 2016 ; Wang X. et al, 2018 ) and interstitial cells ( Ren et al, 2018 ). It is worth noting that Ghrelin seemed showing more effect on RWPE-1 than WPMY-1.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, YIL-781 attenuates prostate enlargement in HFP and TP BPH mice, WP1066 blocks ghrelin-induced cell proliferation and apoptosis inhibition, increased Bcl2 and decreased BAX expression also strengthens the evidence that Ghrelin promotes cell proliferations while inhibits apoptosis in the prostate gland through Jak2/STAT3 pathway. Effect of Ghrelin on apoptosis in prostate cells may be consistent with results in previous study that Ghrelin attenuated apoptosis of human micro vascular endothelial cells induced by high glucose/high lipid ( Liao et al, 2017 ),endothelial and vascular of cardiovascular system ( Lilleness and Frishman, 2016 ; Wang X. et al, 2018 ) and interstitial cells ( Ren et al, 2018 ). It is worth noting that Ghrelin seemed showing more effect on RWPE-1 than WPMY-1.…”
Section: Discussionsupporting
confidence: 91%
“…As previously reported, TNF-α could induce Caco-2 cells' apoptosis by downregulating the expression of ghrelin (Ren et al, 2018). Therefore, we hypothesized that ghrelin administration could inhibit the apoptosis of Caco-2 cells induced by TNF-α.…”
Section: Ghrelin Inhibits the Apoptosis Of Caco-2 Cells Induced By Tnmentioning
confidence: 74%
“…Increasing evidence has proved the genetic association between TNF-α and UC ( Smillie et al, 2019 ). Moreover, increased TNF-α levels have been noted in patients with UC ( Ren et al, 2018 ). It has been reported that TNF-α administration could promote interstitial cells of Cajal (ICC) apoptosis and UC progression, along with the downregulation of ghrelin ( Ren et al, 2018 ), indicating that ghrelin could play a protective role against UC by inhibiting cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…4(d-f)) were significantly enhanced by hypoxic stimulation and inhibited after PDTC treatment. We further treated both of KFs and NFs with 40 ng/mL of TNF-α to induce NF-κB activation as previous described [25], and found that the expression of p-Smad2/3 were increased even when KFs were in normoxia condition (Supplemental Figure 2(b)), thus suggesting that NF-κB was likely to crosstalk with Smad2/3 pathway. It has been reported that NF-κB could induce miR-148a to sustain TGF-β/Smad signaling activation in cancer cells [26].…”
Section: Hif-1α Activated the Tlr/myd88/nf-κb Pathway And The Downstrmentioning
confidence: 81%